Dietary intake and breast cancer risk in black South African women: the South African Breast Cancer study. Issue 5 (1st February 2019) - Jacobs, Inarie; Taljaard-Krugell, Christine; Ricci, Cristian; Vorster, Hester; Rinaldi, Sabina; Cubasch, Herbert; Laubscher, Ria; Joffe, Maureen; van Zyl, Tertia; Norris, Shane A.; Romieu, Isabelle
Abstract: Incidence rates of breast cancer (BC) are increasing in South Africa. The aim of this study was to investigate the association between dietary intake and BC risk in black South African women. The study population included 396 BC cases and 396 population-based controls matched on age and residence, participating in the South African Breast Cancer study. Diet was assessed using a validated quantified FFQ from which twelve energy-adjusted food groups were formed and analysed. OR were estimated using conditional logistic regressions, adjusted for confounding factors, comparing highest v. lowest median intake. Fresh fruit consumption showed an inverse association with BC risk (OR=0·3, 95 % CI 0·12, 0·80) in premenopausal women, whilst red and organ meat consumption showed an overall inverse association with BC risk (OR=0·6, 95 % CI 0·49, 0·94 and OR=0·6, 95 % CI 0·47, 0·91). Savoury food consumption (sauces, soups and snacks) were positively associated with BC risk in postmenopausal women (OR=2·1, 95 % CI 1·15, 4·07). Oestrogen receptor-positive stratification showed an inverse association with BC risk and consumption of nuts and seeds (OR=0·2, 95 % CI 0·58, 0·86). Based on these results, it is recommended that black South African women follow a diet with more fruit and vegetables together with a decreased consumption of less energy-dense, micronutrient-poor foods such as savoury foods. More research is necessary to investigate the association between BC risk and red and organ meat consumption. Affordable and practical methods regarding these recommendations should be implemented within health intervention strategies.